Hubungan Internal Locus of Control dan Democratic Leadership Style dengan Organizational Citizenship Behaviour Pada Personel Satuan Brigade Mobil Kepolisian Daerah Sumatera Utara - Emil Salim; M. Rajab Lubis; Sjahril Effendy (Universitas Medan Area, 2021)
This study aims to determine (1) the relationship between Internal Locus of Control and Organizational Citizenship Behavior in North Sumatra Police Mobile Brigade Unit Personnel; (2) The relationship between the Democratic Leadership Style and the Organizational Citizenship Behavior of the North Sumatra Police Mobile Brigade Unit Personnel; (3) Relationship, internal locus of control and Democratic Leadership Style with Organizational Citizenship Behavior in North Sumatra Police Mobile Brigade Unit Personnel. This research uses a quantitative approach using instruments, namely the Internal Locus of Control scale, the Democratic Leadership Style Scale and the Organizational Citizenship Behavior Scale. The data analysis technique used is multiple regression analysis. The results of the study can be concluded that there is a significant relationship between Internal Locus of Control and Democratic Leadership with Organizational Citizenship Behavior in North Sumatra Police Mobile Brigade Unit personnel indicated by a positive relationship between Internal Locus of Control and Democratic Leadership Style with Organizational Citizenship Behavior, this is indicated by the coefficient Freg = 42.451; sig 0.001. Based on the results of this study, the proposed hypothesis is accepted. b). there is a positive relationship between Internal Locus Of Control with Organizational Citizenship Behavior with a correlation coefficient of rx1y = 0.581; sig 0.001; and the weight of the effective contribution is 33.8%. c). There is a positive relationship between Democratic Leadership Style and Organizational Citizenship Behavior, with a correlation coefficient of rx2y = 0.500; sig 0.001; with an effective contribution weight of 25%. The total effective contribution of the two independent variables to Organizational Citizenship Behavior is 36.6%. d). From these results it is known that there are still 63.4% influence of other variables on Organizational Citizenship Behavior.